Mental health, self-rated health, risky sexual behaviour, alcohol use, and drug use among students who intend to spend a semester abroad – a cross-sectional study - Danehorn, Emil; Peterson, Ulla; Oscarsson, Marie; Smirthwaite, Goldina; Swahnberg, Katarina (Frontiers in Public Health, 2023)
Aim: Our aim was to investigate potential differences in mental health, self-rated health, risky sexual behaviour, alcohol use, and drug use between (1) Prospective exchange students and campus students separated by sex, and (2) male and female students as a group. Method: Comparative cross-sectional design using an online survey containing the following instruments: Knowledge, Attitudes, and Sexual Behaviour in Young People in Sweden; Self-Rated Health Questionnaire; and General Health Questionnaire 12. One-hundred and fourteen prospective exchange students and 451 campus students participated in the study. Results: Male prospective exchange students rated their mental health as being better and had used cannabis more often compared with female prospective exchange students. Male prospective exchange students also rated their mental health as being better than male campus students. Female students, in general, rated their mental health as worse than male students. A larger proportion of male prospective exchange students had sex together with alcohol compared with male campus students, and a larger proportion of female prospective exchange students had sex with a new partner and drank more alcohol compared to female campus students. Conclusion: The result shows that risky alcohol use and sexually risky behaviour is prominent among prospective exchange students. It is possible that they will continue, and even increase their risky behaviour while abroad as they find themselves in a new social context, and free from influence of the rules and restrictions that they might have at home. With limited knowledge of the local culture, native language, and in an unfamiliar environment, it is possible that the risks will be enhanced and possibly decrease their health. This highlights the need for proactive interventions, conceivably with some variations in content between sexes.